An assessment of bryophytes as bio-indicators of unhealthy environments and as a remedial model for heavy metals’ toxicity - Mat Ali, Qurratu Aini; Othman, Rashidi; Hanifah, Nurul Azlen; Mohd Hatta, Farah Ayuni; Wan Sulaiman, Wan Syibrah Hanisah; Mohd Latiff, Nur Hanie; Ramya, Razanah (Nova Science Publishers, Inc., 2024)
Bryophytes are found on every continent and in all terrestrial ecosystems, from tropical rainforests to arid deserts and polar tundra. Bryophytes perform a vital role in averting soil erosion and preserving significant amounts of water, thereby regulating the water budget of local ecosystems. Bryophytes are bioindicators that accumulate and exhibit elevated levels of heavy metals and other pollutants discharged in water due to natural and anthropogenic sources. Bryophytes have various properties that make them appropriate for supervising water pollutants. These species do not have real roots, and they gather nutrients required for crucial procedures from wet and dry deposition. Biomonitoring with bryophytes is based on the fact that these species have been proven to gain most of their nutrients directly from wet or dry deposition. They can clearly indicate water deposits and are well-suited to heavy metal pollution at an extended time scale. The broad and, in some cases, diverse distribution of many bryophytes from gametophytes species comprise dominant plants among the Earth’s most adaptable taxa. Bioindicators are one of the interesting ways to track water pollution on a large space and time scale due to extremely low sampling costs. Bioindicators are living organisms that can be used to state the health condition of an ecosystem. Certain organisms are very sensitive to pollution in their environment or surroundings. Regardless of long-term pollutants, the organism may change its morphology, physiology, and behavior or die in a worst-case scenario. Most of the time, living organisms can be used to indirectly measure levels of chemicals within their environments. Therefore, this chapter’s findings will enable us to detect or predict specific plant changes due to their environment and track their evolution as a function of time.